Alexithymic trait is associated with right IFG and pre-SMA activation in non-emotional response inhibition in healthy subjects. (29th September 2017) - Gavazzi, Gioele; Orsolini, Stefano; Rossi, Arianna; Bianchi, Andrea; Bartolini, Emanuele; Nicolai, Emanuele; Soricelli, Andrea; Aiello, Marco; Diciotti, Stefano; Viggiano, Maria Pia; Mascalchi, Mario
Highlights: Healthy subjects underwent fMRI using a Go/Nogo task with stimuli devoid of emotional valence. Alexithymic trait was measured with the Toronto Alexithymic Scale (TAS-20) questionnaire. In correctly inhibited trials, the TAS-20 z-score positively correlated with the BOLD activation in right IFG and pre-SMA. Right IFG and pre-SMA BOLD activation may reflect a compensatory phenomenon, allowing a correct response inhibition correlated with increasing TAS-20 z-score. Abstract: Event-related fMRI studies have explored emotion inhibitory processes in alexithymic individuals and have demonstrated abnormal BOLD activations in the processing of emotional stimuli. So far, no study has explored the relationship between the alexithymic trait and the general inhibition process, namely utilizing stimuli devoid of emotional valence. In this study 26 healthy subjects were administered the Toronto Alexithymic Scale (TAS-20) questionnaire to measure the alexithymic trait and performed an event related Go/Nogo task build up with letters during fMRI acquisition. We found no correlation between the TAS-20 z-score and the reaction times during the Go/Nogo task. Conversely, we observed a positive correlation between the degree of alexithymic trait −measured with the TAS-20 and the Nogo-Go activation of the right Inferior Frontal Gyrus and the right pre-Supplementary Motor Area. These data suggest that the general process of response inhibition may be modulated by the individual degree of alexithymic trait. We propose that such a relationship could reflect a compensatory mechanism implemented by participants with higher degree of alexithymic trait to reach a correct inhibition.